2012
DOI: 10.1080/15305058.2011.643517
|View full text |Cite
|
Sign up to set email alerts
|

Test Length and Decision Quality in Personnel Selection: When Is Short Too Short?

Abstract: Personnel selection shows an enduring need for short stand-alone tests consisting of, say, 5 to 15 items. Despite their efficiency, short tests are more vulnerable to measurement error than longer test versions. Consequently, the question arises to what extent reducing test length deteriorates decision quality due to increased impact of measurement error. A distinction was made between decision quality at the group level and the individual level. Using simulations, we found that short tests had a large negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 45 publications
(45 reference statements)
1
50
0
10
Order By: Relevance
“…Loss of measurement precision means that decisions about individuals are more uncertain to a degree that uncertainty may become unacceptable for many decisions. The result may be a large number of decision errors (Emons et al, 2007;Kruyen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of measurement precision means that decisions about individuals are more uncertain to a degree that uncertainty may become unacceptable for many decisions. The result may be a large number of decision errors (Emons et al, 2007;Kruyen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…First, Emons et al (2007) and Kruyen et al (2012) consistently found minor effects of number of response categories on individual decision making. Therefore, the results based on items with five response categories can be generalized to items having other numbers of categories.…”
Section: Discussionmentioning
confidence: 95%
“…using Crobach's alpha), it is frequently desirable to predict the reliability of a test score of a test that measures the same construct but has a different length. For example, in recent years there is an increasing interest in short or shortened tests (Kruyen, Emons, and Sijtsma 2012). A recent literature review is presented in Kruyen, Emons, and Sijtsma (2013).…”
Section: Introductionmentioning
confidence: 99%